Combining Growth Factor and Bone Marrow Cell Therapy Induces Bleeding and Alters Immune Response After Stroke in Mice. Issue 3 (March 2016) - Strecker, Jan-Kolja; Olk, Joanna; Hoppen, Maike; Gess, Burkhard; Diederich, Kai; Schmidt, Antje; Schäbitz, Wolf-Rüdiger; Schilling, Matthias; Minnerup, Jens
Abstract : Background and Purpose—: Bone marrow cell (BMC)–based therapies, either the transplantation of exogenous cells or stimulation of endogenous cells by growth factors like the granulocyte colony–stimulating factor (G-CSF), are considered a promising means of treating stroke. In contrast to large preclinical evidence, however, a recent clinical stroke trial on G-CSF was neutral. We, therefore, aimed to investigate possible synergistic effects of co-administration of G-CSF and BMCs after experimental stroke in mice to enhance the efficacy compared with single treatments. Methods—: We used an animal model for experimental stroke as paradigm to study possible synergistic effects of co-administration of G-CSF and BMCs on the functional outcome and the pathophysiological mechanism. Results—: G-CSF treatment alone led to an improved functional outcome, a reduced infarct volume, increased blood vessel stabilization, and decreased overall inflammation. Surprisingly, the combination of G-CSF and BMCs abrogated G-CSFs' beneficial effects and resulted in increased hemorrhagic infarct transformation, altered blood–brain barrier, excessive astrogliosis, and altered immune cell polarization. These increased rates of infarct bleeding were mainly mediated by elevated matrix metalloproteinase-9–mediated blood–brain barrier breakdown in G-CSF- and BMCs-treated animals combined with an increased number of dilated and thus likely more fragile vessels in the subacute phase after cerebral ischemia. Conclusions—: Our results provide new insights into both BMC-based therapies and immune cell biology and help to understand potential adverse and unexpected side effects. Abstract : Supplemental Digital Content is available in the text.